Football clubs’ sports performance in the context of their market value and GDP in the European Union regions - Klobučník, Michal; Plešivčák, Martin; Vrábeľ, Milan (Bulletin of Geography. Socio-economic Series, 2019)
The aim of the study is to evaluate the relationship between the sporting success of football clubs, their market value and the economic performance of the regions they are located in. All member states of the European Union are under consideration, taking into account the success of the clubs in the highest-ranked male national football competitions and in European cups. The data are processed at NUTS 2 level over a period of one decade (2007–2016). From a methodological point of view, it is beneficial to construct original indexes of clubs’ sporting performance – both at the national level, and an overall one that also takes into account results in international (European) competition. To determine the existence of a link between the sporting performance of the club, its market value and the economic performance of the regional level unit it is located in (measured by gross domestic product), correlation and regression analysis is utilised. For example, the results show a high positive statistical link between a club’s sporting performance and its market value, but a relevant direct statistical link has also been confirmed between the economic performance of the region and the market value of the club, with respect to its sporting success. However, the analysis also showed that the club of a relatively poor region (from a pan-European point of view) could reach above-average results at the highest European level, and vice versa – a club with a high market value, from an economically highly over-developed region, could lag behind.